Beyond internal control over financial reporting : the Chinese experience - Yang, Daoguang, 1987- (Routledge, 2024)
"By examining two different modes of internal control and the fundamentals of risk management, this book analyses the role of internal control in finance, investment, dividend allocation and corporate strategies through China's experience. In doing so, it confirms the effectiveness and superiority of internal control in operation and management. The book compares the various internal control methods used in China and the USA, namely, operation and management-focused versus financial reporting-oriented approaches. It also discusses the differences in corporate risk attitudes and behaviours under the two approaches. The author then proposes the hyper-correction hypothesis and the trimming hypothesis. Empirical findings regarding corporate cash policy, mergers and acquisitions, tax avoidance, and diversification strategy reveal that internal control in China does not result in undue risk aversion but instead manages enterprise risk within a reasonable threshold. These results support the Trimming Hypothesis and demonstrate that internal control is a useful risk management tool. The title will appeal to students, academics and accounting professionals interested in internal control (risk management), accounting, auditing and corporate finance, regulation and governance"-- Provided by publisher.
Keywords: Auditing, Internal -- China.; Accounting -- China.; Financial statements -- China.; Financial risk management -- China.; elektronické knihy; electronic books